2020
DOI: 10.1111/jce.14822
|View full text |Cite
|
Sign up to set email alerts
|

The coronary artery calcium score correlates with left atrial low‐voltage area: Sex differences

Abstract: Introduction:In patients with coronary artery disease, a high coronary artery calcium score (CACS) correlates with atrial fibrillation (AF); however, the association between left atrial (LA) remodeling progression and coronary arteriosclerosis is unclear. This study aimed to evaluate the relationship between LA remodeling progression and the CACS. Methods: This retrospective study enrolled 148 patients with AF (paroxysmal AF, n = 94) who underwent catheter ablation. Voltage mapping for the left atrium and coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…However, it is noted in existing literature that patients with CAD have a higher risk of developing AF 28,29 . Hojo et al 30 reported that a high coronary artery calcium score, as measured by coronary CT, serves as an independent predictor of LVZs, with this association being particularly pronounced in men. The arterial supply to the LA is primarily provided by branches originating from the right coronary artery or the left circumflex artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noted in existing literature that patients with CAD have a higher risk of developing AF 28,29 . Hojo et al 30 reported that a high coronary artery calcium score, as measured by coronary CT, serves as an independent predictor of LVZs, with this association being particularly pronounced in men. The arterial supply to the LA is primarily provided by branches originating from the right coronary artery or the left circumflex artery.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noted in existing literature that patients with CAD have a higher risk of developing AF. 28,29 Hojo et al 30 in conjunction with ventricular infarctions and this is also associated with supraventricular arrhythmias. 31 Research conducted on pigs has also demonstrated that atrial infarctions induced in these animals correspond to LVZs detected through voltage mapping.…”
Section: Coronary Artery Diseasementioning
confidence: 99%